2021
DOI: 10.1128/msystems.00644-21
|View full text |Cite|
|
Sign up to set email alerts
|

Building Natural Product Libraries Using Quantitative Clade-Based and Chemical Clustering Strategies

Abstract: Natural product drug discovery efforts rely on libraries of organisms to provide access to diverse pools of compounds. Actionable strategies to rationally maximize chemical diversity, rather than relying on serendipity, can add value to such efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Both methods were performed utilizing the online metabolomics database and processing servers provided by GNPS [ 17 ]. Based on prior literature, quantification values for each sample were subsequently normalized using rarefaction based on minimum intensity of 1e8 [ 48 ]. This data was further scaled for integration into the multi-omic feature set.…”
Section: Methodsmentioning
confidence: 99%
“…Both methods were performed utilizing the online metabolomics database and processing servers provided by GNPS [ 17 ]. Based on prior literature, quantification values for each sample were subsequently normalized using rarefaction based on minimum intensity of 1e8 [ 48 ]. This data was further scaled for integration into the multi-omic feature set.…”
Section: Methodsmentioning
confidence: 99%
“…This process, which requires painstaking efforts to repeatedly sterilize the cutting and sample manipulation tools (e.g., scissors, forceps, scalpels, dissection probes, pastry or pasta cutters, and other devices) necessitates that even experienced researchers are limited to processing roughly 4–6 samples per minute (these values are based on our personal experiences and have been further substantiated via communications with other mycologists). Since a single plant leaf may harbor dozens of symbionts, with some inhabiting only limited portions of the host tissue, it can become an arduous task to systematically sample even a single plant specimen, let alone explore large numbers of different plants. Our team viewed such limitations as an opportunity to eliminate this bottleneck, which in turn would improve efforts to sample diverse assemblages of plants and secure the sizable numbers of isolates required for successful bioactive natural-product discovery efforts …”
Section: Resultsmentioning
confidence: 99%
“…45−47 Our team viewed such limitations as an opportunity to eliminate this bottleneck, which in turn would improve efforts to sample diverse assemblages of plants and secure the sizable numbers of isolates required for successful bioactive naturalproduct discovery efforts. 48 These challenges inspired our group to explore the use of laser-based precision cutting methods for preparing plant tissues because such an approach could in theory eliminate the need to physically touch a plant specimen once it has undergone an initial round of surface sterilization. After testing a variety of methods and devices, we found that a simple, hobby-grade, or light-duty commercial laser apparatus offered the best option for engineering a cost-effective plant specimen cutting tool.…”
Section: Development Of a Novel Endophyte Procurementmentioning
confidence: 99%
“…31 Complicating this matter further, it was shown that deep sampling of a single fungal genus could uncover surprisingly high levels of chemical diversity within a taxonomically restricted group. 32 Notwithstanding these and other efforts, some of the motives offered to support various microbial sourcing strategies for natural products discovery remain largely untested.…”
mentioning
confidence: 99%
“…This logic has been used to justify the pursuit of microbes and their natural products from a variety of curious and extraordinary locations. ,, , However, recent efforts to compare microbially derived metabolites across two major biomes (i.e., terrestrial versus marine environments) revealed extensive overlap in the natural products being produced . Complicating this matter further, it was shown that deep sampling of a single fungal genus could uncover surprisingly high levels of chemical diversity within a taxonomically restricted group . Notwithstanding these and other efforts, some of the motives offered to support various microbial sourcing strategies for natural products discovery remain largely untested.…”
mentioning
confidence: 99%